The relationship between the work and language (Research, Society and Development, 2021)
The general objective of this research is to enable an investigation of the relationship between work and language. The specific objectives consist of: 1) Understanding the category of work from the ontological perspective of the social being; 2) Debate about the relationship between language and the reproduction of the social being as a necessary category for the human being and the socio-historical process of human development. The research is based on the ontological method: it assumes that objectivity determines knowledge. From the point of view of objectives, it is an exploratory research, with bibliographic technical procedures. And it will feature the contribution of theorists such as: Lessa (2016), Tonet (2016), Bakhtin (2014), among other relevant authors in the literature. It is concluded that work is the primary category of the human being, involves social reproduction and also requires other forms of activities for the formation and development of man in society; there is a close connection between work and language, which spontaneously intervenes in human development since, through it, men idealize considerations, conduct information, resolve disorders, and relate to their peers.